Marketing System of Non-Timber Forest Products:-The Case of Palmyra Palm in North-Eastern Nigeria (2009)
"This study investigated the marketing system of Palmyra Palm products in North-eastern Nigeria to; identify its marketable products, channels of distribution and roles of market participants, and also assess its marketing facilities in North-eastern Nigeria. Data were generated through market surveys and interviews on 203 respondents selected randomly from Adamawa, Bauchi and Yobe markets. The generated data were analysed using descriptive statistics where appropriate. Marketing system focusing market organization was analyzed qualitatively by observing the marketing channels, roles of market participants and marketing facilities. The results revealed that exchange and ownership of title to products occurred at the local markets (54.0%), farmers' homes (37.7%), and farmers' farms (6.2%), and inter-states' markets (2.1%). The marketing channel of Palmyra palm was highly decentralised and thus the marketing system was expected to be operationally efficient. However, because of poor road network, high transportation cost and poor marketing facilities, the marketing system was adjudged operationally inefficient. Market participants introduced flaws in the marketing system; farm-gate middlemen dominated marketing operations, commissioned buying agents over-depended on wholesalers for capital, and there was collusion in price determination. Marketing facilities namely market places, storage, processing, transportation and packaging were crude and inadequate, while credit facilities were virtually absent. To address these inadequacies, the study recommended provision of improved marketing facilities and communication gadgets, formation of consumer co-operative organizations to check the excesses of the middlemen in the market and more research into the marketing of Non-timber forest resources."